Hydrocarbon generation characteristics and potential of liptinite-rich coal in China - Yuting Yin; Dongdong Wang; Lei Lan; Youchuan Li; Haiyan Liu; Zengxue Li; Yan Liu (Energy Geoscience)
Coal-measure source rocks may play an important role in hydrocarbon generation in petroliferous basins where coal seams are well developed. Hydrocarbon generation characteristics and potential of coal-measure source rocks have been well documented for continental petroliferous basins, while the understanding of coal-measure source rocks in offshore basins is yet to be delved into. Significant oil exploration breakthroughs have been made in the well-developed coal measures of Turpan–Hami Basin (THB), a typical continental petroliferous basin in northwestern China. In this study, a comparative analysis is conducted on the Paleogene coal seams in the Zhu I Depression (ZID), located in the northern part of the South China Sea, and the Jurassic coal seams in the THB in terms of genetic conditions, mineral composition, and hydrocarbon generation potential. The geological understandings are obtained as follows. Both the coal-forming periods during the deposition of the ZID and THB were of a warm and wet climate type. The Paleogene coal-forming environments during the deposition of the ZID mainly include peat swamp in the upper plain and interdistributary bays in the lower plain of the braided river delta, along with littoral shallow lakes. As a whole, the coal seams are characterized by multiple layers, thin single layer thickness and poor stability, while those in the upper plain peat swamp of the braided river delta have relatively larger single layer thickness but relatively fewer number of layers. The Jurassic coal-forming environments in the THB include peat swamp in the upper delta plain, lower delta plain, and inter-delta bay. The coal seams formed in the lower delta plain are the most stable, while those in the inter-delta bay are the thickest. The ZID coal has a higher vitrinite content (averaging 76.11 %) and liptinite content (averaging 10.77 %) compared to its THB counterpart, which has an average vitrinite content of 68.28 % and average liptinite content of 7.61 %. The kerogen of the ZID coal is mainly of type II1, while that of the THB coal mainly of type II2, followed by type Ⅲ. Both the ZID and THB coals have entered the oil-generation window, as indicated by their maximum vitrinite reflectance values (Ro, max, %), reflecting good oil generation capacity. However, the hydrocarbon generation potential of the ZID coal is higher than that of the THB.